Agency problem, managerial incentive and financial controlling instrument: a brief review for agenda study in Malaysia - Ghasemi, Maziar; Ab Razak, Nazrul Hisyam; Hassan, Taufiq (Universiti Putra Malaysia Press, 2015)
Although the agency theory has been widely used across a variety of corporate finance concepts for the past three decades, little work has been undertaken with regard to how the agency theory could be used to explain simultaneous interrelation among internal solutions for Agency problem. In addition, no general consensus has emerged after many years of investigation and scholars can often disagree about the same empirical evidence. Among other, potential endogeneity of the agency mechanisms, as well as cultural and structural differences between developed and developing markets, has been stated to cause the complexity of corporate governance around the world. This article reviews the theoretical and empirical literature addressing causal effects of managerial incentives and financial controlling instrument due to agency problem. At the same time, the article aims to improve the understanding of how these instruments affect each other. The main part of the discussion is related to the evaluation of theoretical aspects of internal Agency solution and their interrelations, as well as the experiential studies in different countries. As such, specification of Malaysian market is surveyed separately to highlight the need for multi-theoretic process and interrelation effects in future research on corporate agency problems in the Malaysian context.